Analysis of Socio-Economic Levels and Patient Satisfaction Levels on Revisit Intention at the Emergency Room of Pradipa Medika Hospital - Sygih Pratama; Cecep Darmawan; Rinawati Rinawati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The Emergency Department (ED) is a critical unit within hospitals, serving as the frontline for handling patients in emergency and critical conditions. The success of ED services depends not only on the quality of medical actions but also on patient satisfaction and their intention to revisit. This study aims to analyze the influence of socioeconomic level and patient satisfaction on patients' revisit intention to the ED of Pradipa Medika Hospital. This research uses a quantitative method with a cross-sectional approach involving 229 respondents selected through probability sampling. Data were collected using a validated and reliable questionnaire and analyzed using multiple linear regression. The results showed that socioeconomic level and patient satisfaction significantly affect patients' revisit intention. Patient satisfaction, particularly in the dimensions of reliability, assurance, tangibles, empathy, and responsiveness, is the main determinant driving patient loyalty to ED services. The study emphasizes the importance of improving hospital service quality by considering patients' socioeconomic aspects as a strategy to strengthen loyalty and patient retention.